Bawang Merah di Pekarangan: Mewujudkan Kemandirian Pangan Desa Tanjung Baru Petai - Erni Hawayanti Hosiah; Neni Marlina; Gusmiatun Gusmiatun; Maria Lusia; Berliana Palmasari; Dessy Tri Astuti; Nico Syahputra; Railia Karneta; Joni Phillep Rompas; Haperidah Nunilahwati (Universitas Muhammadiyah Palembang, 2025)
High dependency on seasonal harvests and limited access to quality food are challenges for the agrarian community in Tanjung Baru Petai Village, Ogan Ilir. This community service program aims to overcome these challenges through shallot cultivation in home yards, focusing on the empowerment of the Women Farmers Group (KWT). The method used is a participatory approach which includes socialization, technical training on shallot cultivation in polybags, the application of simple technology (organic compost), and continuous mentoring. Through the training, the community, especially housewives, gained independent cultivation skills on limited land. The program is expected to result in self-sufficient shallot gardens in residents' yards, improve skills, and strengthen household food security. The sustainability of the program is supported by the formation of home-yard farmer groups and the involvement of the village government for the replication and diversification of horticultural crops.